Robackia Saeher from China (Diptera: Chironomidae) - Yan, Chun Cai; Wang, Xinhua (Zootaxa, 2006)
Robackia parallela sp. n. from Oriental China is described and illustrated as male. It differs from other known species of the genus by having a low antennal ratio, a parallel-sided superior volsella, and abdomen with dark brown marks. Chinese males of R. pilicauda Sæther are examined and figured. A key to all males of Robackia is given.